THE INFLUENCE OF WORK-LIFE BALANCE AND BURNOUT ON EMPLOYE WORK PRODUCTIVITY AT PT XYZ (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to analyze the effects of work-life balance and burnout on employee productivity at PT XYZ, an automotive manufacturing company characterized by high production pressure and demanding shift schedules. This study employed a quantitative approach using primary data collected through a Likert-scale questionnaire distributed online to 85 respondents selected through simple random sampling. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that work-life balance had no significant partial effect on work productivity, while burnout had a significant partial effect with a positive relationship at the 10 percent significance level, which can be explained through the concept of eustress. Simultaneously, both variables were found to significantly affect work productivity, although the adjusted R square value of only 0.053 indicates that many other factors outside this study also influence employee productivity. These findings offer practical implications for PT XYZ to develop employee psychological well-being programs, such as an Employee Assistance Program, to prevent the long-term negative effects of burnout, while also opening opportunities for future research to explore other variables relevant to work productivity in the manufacturing sector.